Frequency and Culture Sensitivity for Bacteremia During Febrile Neutropenia in Children with Acute Lymphoblastic Leukemia. Do Age and Gender Matter? - Bin Mehmood, Rana Usama; Aslam, Afra; Ayaz, Saeed Bin; Choudhry, Shehla; Javed, Sidra; Ashraf, Khaula (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To determine the frequency of bacteremia and its association with age and gender in febrile neutropenic children suffering from acute lymphoblastic leukemia and identify the commonest pathogens and their antibiotic susceptibility identified on blood cultures. Study Design: Cross-sectional analytical study Place and Duration of Study: Pediatrics Inpatient Department, Shifa International Hospital, Islamabad Pakistan, from Sep 2018 to Mar 2019. Methodology: Children with acute lymphoblastic leukemia aged 1-12 years, presenting with temperature >100ºF and absolute neutrophil count of <500 cells/µL were enrolled. An automated blood culture system was used and Clinical and Laboratory Standards Institute Guidelines 2017 were used for susceptibility testing. Antibiotics were started empirically in all cases and changed after susceptibility testing. Results: A total of 62 children were enrolled. The mean age was 8.6 ± 2.4 years. Majority of the children i.e., 32 (51.6%) were females. The frequency of bacteremia was 16 (25.8%) and there was no significant association with age or gender (p=0.475 and p=0.881 respectively). Majority of the isolates were gram-positive. The organism isolated in the highest frequency was Methicillin-Resistant Staphylococcus Epidermidis (MRSE) 5 (31.25%). Susceptibility to Vancomycin was present in 10 isolates while seven isolates were sensitive to penicillins/cephalosporins. Conclusion: Bacteremia, primarily caused by gram-positive bacteria was found in 25.8% of our sample and was uninfluenced by age or gender. MRSE was the most frequent isolate. The bacterial isolates were susceptible primarily to vancomycin and penicillins/cephalosporins.